A Systems‐Level Roadmap for Biomass Thermal Fractionation and Catalytic Upgrading Strategies. Issue 1 (15th June 2016) - Herron, Jeffrey A.; Vann, Tyler; Duong, Nhung; Resasco, Daniel E.; Crossley, Steven; Lobban, Lance L.; Maravelias, Christos T.
Abstract: Although multistage thermal decomposition (fractionation) of biomass with catalytic upgrading is a promising strategy of achieving sustainable fuels production, the number of thermal decomposition stages, their conditions, and the optimal catalytic upgrading chemistries are not known. In this paper, we use conceptual process modeling to propose a general roadmap for the design of a biorefinery by employing these technologies. The overall process considered includes a biomass pretreatment system, a (multistage) thermal decomposition system in which the biomass in decomposed into various fractions, a fraction upgrading system, and a combustion system. We focus primarily on the design of the thermal decomposition and fraction upgrading systems. The goal of our work is to demonstrate the key trade‐offs between various process options and to identify important areas for improvement. In general, increasing the complexity of the fraction upgrading systems increases the ultimate yield of C6+ products, though there are diminishing returns on the increase in product yield versus the complexity of the catalytic upgrading sequences. The choice of the number of thermal decomposition stages is not simple and requires careful consideration of the chemistries available to upgrade different components and the relative abundances of these different components. Therefore, the optimal design of the thermal decomposition and fraction upgrading systems cannot be done independently. Abstract : Mapping it out : We use conceptual process modeling to propose a general roadmap for the design of a biorefinery by employing a multistage thermal decomposition system of biomass. The choice of the number of thermal decomposition stages and upgrading strategies requires careful consideration of the chemistries available to upgrade the different species in the thermal fractions.